Regulasi Jaminan Produk Halal Sebagai Bentuk Perlindungan Hukum Terhadap Konsumen Muslim Dalam Produk Kosmetik - Adelia, Chafizah; Tarmidzi, Tarmidzi; Saleh, Hairus (el hisbah Journal of Islamic Economic Law, 2025)
For the majority of Muslims, the halal status of a product is very important for those who use it. Halal products are a necessity that is mandatory in Indonesia, not just food and medicine, for women, skin care in the modern era is now an obligation to make their appearance attractive. As a Muslim, it is not only halal food that must be kept halal, the care used from hair to feet must also be halal. This research uses the Normative Juridical research method, while the research studied uses legal materials or library materials, which in this case is secondary data. Then the researcher took a qualitative approach which emphasized understanding social phenomena in depth through the individuals involved. Data collection techniques through library studies, documents and archival studies. Data analysis was carried out using a qualitative approach.The results of the study indicate that the regulation of legal protection for Muslim consumers in cosmetic products is quite adequate. However, in its implementation it is not yet effective enough, because there are still cosmetic products that do not have distribution permits. The rights of consumers protected by consumer protection laws have not been fulfilled.